Significance of BAFF/APRIL Expression and Their Receptors in Pediatric Patients With Acute Lymphoblastic Leukemia. Issue 3 (April 2016) - Sun, Baolan; Li, Lin; Xu, Meiyu; Wang, Xudong; Wang, Feng; Ni, Hongbing
Abstract : In this study, we investigated the mRNA expression and protein levels of B-cell activating factor (BAFF)/a proliferation-inducing ligand (APRIL) and their receptors in acute lymphoblastic leukemia (ALL) cell lines and pediatric patients with ALL using real-time polymerase chain reaction, enzyme-linked immunosorbent assay, and Western blotting. The location and level of the BAFF/APRIL proteins in ALL cell lines were also detected by immunofluorescence cytochemistry and flow cytometry. Correlations between plasma protein levels of BAFF/APRIL and primary clinical parameters were analyzed. We found that BAFF/APRIL was highly expressed in pediatric ALL patients and ALL cell lines. The BAFF/APRIL proteins were located on the cell membrane, and the proportion of positive cells and mean fluorescence intensity were significantly higher than in the healthy control group ( P <0.05). The mRNA expression and protein levels of BAFF/APRIL and their receptors in untreated ALL children were significantly higher than in healthy controls ( P <0.05) as well as were significantly reduced in the remission group ( P <0.05). The plasma protein levels of BAFF/APRIL were positively correlated with the white blood cell count, lactate dehydrogenase, and serum ferritin. Abnormal levels of BAFF/APRIL in pediatric ALL suggest that BAFF/APRIL are associated with the development and progression of ALL in children and may provide information for the development of BAFF-based and APRIL-based targeted therapies. Abstract : Supplemental Digital Content is available in the text.